PENGARUH MODEL PEMBELAJARAN CONNECTION-ORGANIZING-REFLECTING-EXTENDING (CORE) TERHADAP PENINGKATAN PEMAHAMAN KONSEP DAN KEMAMPUAN KONEKSI MATEMATIS SISWA KELAS VIII SMP NEGERI SE-KOTA PADANG - M.Pd, Mulyani (RC-INSTITUT, 2018)
This study was aimed at examining the effect of Connection-Organizing-Reflecting-Extending Learning Model (CORE) toward the improving of the second grade of Junior High school students’ Understanding of Mathematical Concepts and Connections ability in Padang. This research was a Quasi Experiment. The population was all eighth grade students of Padang State of Junior High school accredited A as listed in the second semester of academic year 2013/2014. Technique of sampling was random sampling. The samples in this study VIII.3 of SMP Negeri 25 Padang as the experimental class and VIII.4 of SMP Negeri 12 Padang as the  control class. Data analysis was performed by using the t-test and U-test.The results were obtained some conclusions. Firstly, the increasing of students’ understanding of the concepts who were taught by CORE learning model is better than students who were taught by conventional learning model and the improving of students’ understanding of the concept of students’ medium and low level ability, whereas for high-ability students at the beginning, there is no significant improvement between the experimental and control class. Secondly, the increasing of students’ connective ability that was taught by CORE learning model is better than students who were taught by conventional teaching and the increasing of students’ connective mathematical ability of high, medium and low ability